2013
DOI: 10.1002/pmic.201200193
|View full text |Cite
|
Sign up to set email alerts
|

A physiological and proteomic study of poplar leaves during ozone exposure combined with mild drought

Abstract: The occurrence of high-ozone concentrations during drought episodes is common considering that they are partially caused by the same meteorological phenomena. It was suggested that mild drought could protect plants against ozone-induced damage by causing the closure of stomata and preventing the entry of ozone into the leaves. The present experiment attempts to create an overview of the changes in cellular processes in response to ozone, mild drought and a combined treatment based on the use of 2D-DiGE to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 71 publications
0
13
0
3
Order By: Relevance
“…Besides, other hormonal signals, such as ethylene, gibberellic acid, and jasmonic acid are also important cellular regulators in signal transduction pathway under drought conditions [99,100,101]. Proteomic studies revealed a drought-increased ethylene-responsive transcription factor (ERF) in Gossypium herbaceum [51] and some members of drought-responsive auxin-binding protein (ABP) family in Q. robur [61], Z. mays [41], and polar clones [59]. The ERF gene was found to be induced in G. herbaceum under drought stress [102,103] (Figure 2A).…”
Section: Drought Sensing and Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, other hormonal signals, such as ethylene, gibberellic acid, and jasmonic acid are also important cellular regulators in signal transduction pathway under drought conditions [99,100,101]. Proteomic studies revealed a drought-increased ethylene-responsive transcription factor (ERF) in Gossypium herbaceum [51] and some members of drought-responsive auxin-binding protein (ABP) family in Q. robur [61], Z. mays [41], and polar clones [59]. The ERF gene was found to be induced in G. herbaceum under drought stress [102,103] (Figure 2A).…”
Section: Drought Sensing and Signalingmentioning
confidence: 99%
“…Similarly, MS in Z. mays [41], Sorghum bicolor [202], a drought-tolerant C. dactylon cultivar, as well as SAMS in Populus [59,86], Q. ilex [63], and T. aestivum [35] were increased under drought conditions. The metabolites in the SAM cycle were known to play major roles in methylation of DNA, proteins, and other metabolites, being involved in control of gene expression, cell wall metabolism, as well as the biosynthesis of polyamine and ethylene for stress tolerance [18,203,204].…”
Section: Nitrogen Assimilation and Amino Acid Metabolismmentioning
confidence: 99%
“…O 3 暴露下, 干旱对植物的保护作用仅限于叶片水 平, 但对整株植物而言, 干旱的伤害大于O 3 的伤害 (Alonson et al, 2014;Pollastrini et al, 2014)。此外, 由于O 3 刺激糖基酶类基因表达促进了葡聚糖代谢, 而干旱则是抑制其代谢, 导致两种胁迫下上述代谢 过程并没有受到影响 (Iyer et al, 2013), 减轻了植物 在交互作用下所受到的伤害。因此, O 3 和干旱对植 物的伤害不仅取决于O 3 进入细胞的量 (Heath, 1994), 而且与植物通过酶类和非酶类反应去除氧自由基的 能力 (Manderscheid et al, 1991)及自身防御和修复 过程的活跃度有关 (Sandermann, 1996) (Panek & Goldstein, 2001), 进而影响植 物生长。气孔的响应(关闭)也并不是始终如一的 (Wittig et al, 2007), 如 O 3 诱发的气孔反应滞后 (sluggish) (Paoletti & Grulke, 2010;Hoshika et al, 2012Hoshika et al, , 2014Dumont et al, 2013)所导致的气孔关闭 缓慢 (Pearson & Mansfield, 1993;Karlsson et al, 1995)或气孔导度增大 (Oksanen, 2003), 降低了气孔 在干旱条件下对蒸腾的抑制, 从而扰乱了植物对水 分亏缺的响应 (Hoshika et al, 2014), 导致O 3 和干旱 交互作用下植物的伤害加重 (Retzlaff et al, 2000;Pollastrini et al, 2010 (Buckland et al, 1991;Biehler & Fock, 1996), 使植物受到伤害, 因而干旱和O 3 的复 合胁迫对植物可能是有害的 (Heber et al, 1995)。自 然环境中O 3 与干旱对气孔的交互作用取决于品种 (Pell et al, 1993;Ribas et al, 2005;Biswas & Jiang, 2011;Wagg et al, 2012)、 胁迫出现次序 (Bohler et al, 2013)、胁迫程度(Le Thiec et al, 1994)、一天内胁迫 的 时 段 (Le Thiec et al, 1994) 、 植 物 的 生 长 期 (Alonso et al, 2001;Skärby et al, 1998)以及季节的 变化 (Pell et al, 1993) Thiec et al, 1994;Bohler et al, 2013)…”
unclassified
“…Leontodon hispidus施用外源脱落酸(ABA)后, 渐进 的干旱胁迫会降低气孔导度 (Wilkinson & Davies, 2009), 通过干旱影响气孔对ABA的敏感性和离子 泵, 降低了细胞的膜损伤 (Torsethaugen et al, 1999) (Brendley & Pell, 1998;Pelloux et al, 2001)影响植物 的生理功能, 并导致净光合速率、最大羧化速率以 及气孔导度的降低 (Guidi et al, 2001;Morgan et al, 2003;Biswas & Jiang, 2011)。在卡尔文循环中一些 Bohler et al, 2007Bohler et al, , 2010Bohler et al, , 2013, 使卡尔文循环被激 活。土壤因有效水分减少而降低光合速率也主要是 因为Rubisco活性的降低 (Bota et al, 2004), 进而导 致植物的生长受限 (Huang & Fu, 2000)。 Rubisco对胁 迫的响应往往因植物品种不同和环境的改变而不 同。如水分胁迫下烟草的Rubisco酶类受到抑制降低 了Rubisco活性 (Parry et al, 2002), 而夏栎(Guercus robur)的Rubisco活化酶增加导致Rubisco降解 (Sergeant et al, 2011), Pinus halepensis 的 Rubisco 和 Rubisco活化酶转录的丰度及蛋白含量则并未改变 (Pelloux et al, 2001) (Pelloux et al, 2001)。但也有结果显示P. halepensis的Rubisco活性 并未因O 3 而改变, 而是因干旱显著降低, 使两种胁 迫下Rubisco活性显著降低 (Gerant et al, 1996)(Hatch et al, 1969), 而且PEPc 活性增强可激发三羧酸循环保持氮代谢运行的补偿 机制 (Tietz & Wild, 1991)。PEPc活性的变化不仅取 决于胁迫时间, 而且因品种变化而不同。例如有实 验证实干旱条件下豌豆(Pisum sativum)和Arachis pintoi 中 的 PEPc 活 性 是 增 强 的 (Sharma & Nisha, 1993;Fedina & Popova, 1996), 棉花(Gossypium hirsutum)中PEPc活性表现出降低的趋势 (Pandey et al, 2001), 而P.…”
unclassified
“…A limited number of studies conducted proteomic analysis of plants subjected to combined stresses including drought and ozone in poplar (Bohler et al 2013), drought and heat in Arabidopsis thaliana, barley and Carissa spinarum , Zhang et al 2010, Rollins et al 2013, heavy metals as mercury and salinity in Suaeda salsa (Liu et al 2013) and high temperature and humidity in Portulaca oleracea Introduction 10 compared to each of its individual stress components (Keles and Oncel 2002, Barnabás et al 2008, Zandalinas et al 2016a, Zandalinas et al 2016b. In general, the negative impacts of drought and heat stress are considered not to be additive, pointing to a certain degree of independence between the mechanisms involved in the responses of plants to drought or heat stress .…”
Section: The Importance Of Investigating Abiotic Stress Combinationmentioning
confidence: 99%